The community-level effect of light on germination timing in relation to seed mass: a source of regeneration niche differentiation - Zhang, Chunhui; Willis, Charles G.; Burghardt, Liana T.; Qi, Wei; Liu, Kun; Souza-Filho, Paulo Roberto de Moura [UNESP]; Ma, Zhen; Du, Guozhen (Wiley-Blackwell, 2014)
Within a community, species may germinate at different times so as to mitigate competition and to take advantage of different aspects of the seasonal environment (temporal niche differentiation). We illustrated a hypothesis of the combined effects of abiotic and biotic competitive factors on germination timing and the subsequent upscale effects on community assembly. We estimated the germination timing (GT) for 476 angiosperm species of the eastern Tibetan Plateau grasslands under two light treatments in the field: high (i.e. natural) light and low light. We also measured the shift in germination timing (SGT) across treatments for all species. Furthermore, we used phylogenetic comparative methods to test if GT and SGT were associated with seed mass, an important factor in competitive interactions. We found a significant positive correlation between GT and seed mass in both light treatments. Additionally, small seeds (early germinating seeds) tended to germinate later and large seeds (late germinating seeds) tended to germinate earlier under low light vs high light conditions. Low light availability can reduce temporal niche differentiation by increasing the overlap in germination time between small and large seeds. In turn, reduced temporal niche differentiation may increase competition in the process of community assembly.
Keywords: community assembly; competition; phylogenetic community structure; phylogenetic diversity; phylogenetic signal; resource limitation; temporal niche; Tibetan Plateau